Respon Pertumbuhan Sawi Hijau (Brassica juncea L.) Terhadap Pemberian Pupuk Jadam Microbial Solution (JMS) dan NPK Cair - Zai, Seiman Jaya; Samah, Eri; Harahap, Lutfi Henderlan (UNIVERSITAS LABUHANBATU, 2025)
This study aimed to determine the effect of applying Jadam Microbial Solution (JMS) and liquid NPK fertilizer, both factorially and in combination, on the growth of mustard greens (Brassica juncea L.). The experiment was carried out using a factorial Randomized Block Design (RBD) consisting of two factors. The first factor was JMS application with four levels (J0 = 0 ml/l water, J1 = 100 ml/l water, J2 = 200 ml/l water, J3 = 300 ml/l water), and the second factor was liquid NPK fertilizer with four levels (N0 = 0 ml/l water, N1 = 10 ml/l water, N2 = 15 ml/l water, N3 = 20 ml/l water). Each treatment combination was repeated three times, resulting in 16 treatment combinations. The results showed that JMS application had a significant effect on plant height and number of leaves at all observation times (7, 14, and 21 days after planting/DAP), indicating improved vegetative growth and yield. Liquid NPK fertilizer application also significantly affected plant height and number of leaves at all observation times. The combination of JMS and liquid NPK fertilizer had no significant effect during the early growth stage (7 DAP), but showed significant effects on plant height and number of leaves at 14 and 21 DAP. These findings indicate that factorial application of JMS and liquid NPK fertilizer can enhance the growth of mustard greens, while their combination is effective at certain vegetative growth stages. Keywords: Brassica juncea L., jadam microbial solution, liquid NPK